CoMusicProducer : study of issues and tools in supporting real-time collaborative music production - Liu, Xin. (2011)
Computers and software are playing important roles in modern music production. This has provided opportunities for a number of home based amateur producers to produce music by themselves even without those expensive studio equipments they cannot afford.